Government House - Trinidad - (:unkn) unknown (My University, 2009)
The photography shows the garden of the Government House. In the background, the main building and the St. Ann's hills can be seen. Affixed to the postcard is a British Guiana 1 cent stamp, postmarked December 20, 1905. Printed on the postcard are the words "West Indian View Postcard". Series VI.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; 1905; Botanical gardens--Trinidad and Tobago; Gardens--Trinidad and Tobago; Architecture--Trinidad and Tobago; President's House, The